A case report of successful treatment of herpes encephalitis in second trimester of pregnancy - Ashraf Saber; Mobina Hosein Fakhrabadi; Mahvan Khodaparast; Shadi Bazyar (Mashhad University of Medical Sciences, 2020)
Introduction: Herpes encephalitis is a neurological emergency disorder. In this paper, a case of sporadic herpes encephalitis in a pregnant woman at 26 weeks of gestation was reported. Case presentation: The patient was a 30-year-old pregnant woman with gestational age of 26 weeks that due to decreased consciousness, confusion, failure to answer questions, disorientation, nausea and vomiting, headache on both sides of the temporal region and Dysphoria was admitted in gynecology ward of Bojnourd Bentolhoda Hospital. On admission, vital signs and oxygen saturation were normal. Magnesium sulfate was administered because of suspected neurological symptoms of eclampsia and proteinuria. Brain MRI was performed after 8 hours due to fever, continued disturbance of consciousness and generalized tonic-clonic seizure that bilateral involvement of the temporal and left frontal areas was evident. Electroencephalogram (EEG) showed Sharps waves in the left frontal, which was consistent with seizure disorder. Intravenous acyclovir was administered after convulsions and exacerbation of neurological symptoms. Polymerase chain reaction (PCR) for detection of Mycobacterium tuberculosis complex, Herpes simplex virus 1 and Brucella in Cerebrospinal Fluid was negative. Level of Protein, leukocytes and RBC was increased in CSF analysis. Blood cultures and serum tests for brucellosis (2-mercaptomethanol and Wright's agglutination test) were negative.  PCR was not repeated because of the patient's dissatisfaction. According to the results of laboratory tests, brain MRI and EEG, diagnosis of herpes simplex encephalitis was suggested. The patient improved and was discharged after 14 days of hospitalization. Healthy baby was born by vaginal delivery at 39 weeks of gestation. Conclusion: In the event of neurological symptoms in pregnant women (headache, dizziness, and altered consciousness), an urgent consultation with a neurologist is required to rule out other differential life-threatening diagnoses other than eclampsia such as herpes simplex encephalitis. Since there is no specific guideline for management of viral encephalitis in pregnancy, guidelines designed for non-pregnant women are recommended in these cases.